Ambition : ambient intelligence with emotional behaviour - Ramos, Carlos (2006)
In this paper, we intended to present the Architecture of Ambition System (Ambient Intelligence with Emotional Behaviour for Groups & Social Interaction and Support). The aim of Ambition is to build a ubiquitous system able to exhibit an intelligent and emotional-aware behaviour in the interaction with individual persons and groups. Groups and Social systems will be modelled by intelligent agents that will be simulated considering emotional aspects, to have an idea of possible trends in social/group interactions.